How Should Physical and Social Communication Be in Physical Education and Sports Lessons? - Dadı, Muhammet Munir; Özer Yıldız (MASI Mandiri Edukasi, 2024)
This research examines the views of physical education and sports teachers on parents' perspectives on how physical and social communication should be in physical education and sports lessons. The interview method, one of the qualitative research designs, was used in the research. The research group consists of 28 physical education and sports teachers working in schools affiliated with the Ministry of National Education, using the purposeful sampling method, one of the nonprobability sampling strategies. Research data were collected through a semi-structured interview form developed by the researcher. In the study, the data were evaluated using the content analysis method. According to the results of the research, the category of the effect of communication on physical education and sports lesson, regarding the views of physical education and sports teachers on the parents' perspectives on how physical and social communication should be in physical education and sports lessons, respectively; Considering that it plays an active role in the social development of students, the importance of communication with students increases parents' interest in the lesson, supporting the teacher due to the positive effect of communication on the student, showing a sincere approach to the teacher, thinking that teachers play an active role in solving some problems that families cannot solve, in the eyes of parents, physical education and the increase in the reputation of the sports course, respectively, under the theme of harmful gaze; It has been determined that they express the opinion that the lesson is considered unimportant, that the thought that the children will be harmed eliminates the desire to participate in the lesson.